2001
DOI: 10.1093/bja/87.5.711
|View full text |Cite
|
Sign up to set email alerts
|

Use of multi-plane transoesophageal echocardiography in visualization of the main hepatic veins and acquisition of Doppler sonography curves. Comparison with the transabdominal approach

Abstract: The role of multi-plane transoesophageal echocardiography (TOE) in the visualization of the three main hepatic veins and acquisition of Doppler sonography curves has not been established. We have studied this diagnostic option of TOE in 34 patients during general anaesthesia. The findings were compared with the results of conventional transabdominal sonography (TAS). Using TOE, each of the three main hepatic veins could be visualized in all patients. In contrast, TAS allowed adequate two-dimensional visualizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 32 publications
0
17
0
Order By: Relevance
“…[16][17][18][19][20][21] However, 3 to 27% of patients receiving TEE evaluation of hepatic blood flow are reported to present poor quality sonographic images. 20,21,25) In this study, decreased HVBFI was observed after administration of heparin with one excluded patient (5%, 1/19). Though poor quality of sonographic images may occur, TEE is effective for management of hepatic blood flow in order to investigate drug metabolism.…”
Section: <001mentioning
confidence: 51%
See 1 more Smart Citation
“…[16][17][18][19][20][21] However, 3 to 27% of patients receiving TEE evaluation of hepatic blood flow are reported to present poor quality sonographic images. 20,21,25) In this study, decreased HVBFI was observed after administration of heparin with one excluded patient (5%, 1/19). Though poor quality of sonographic images may occur, TEE is effective for management of hepatic blood flow in order to investigate drug metabolism.…”
Section: <001mentioning
confidence: 51%
“…19,20,[24][25][26] To visualize the hepatic veins, the tip of the probe was advanced into the antrum of the stomach and flexed anteriorly. The Doppler sonography curve was attained by pulsed wave Doppler technique (PWmode).…”
Section: Assessment Of Hepatic Blood Flowmentioning
confidence: 99%
“…Methods for the two-dimensional (2D) identification and the PWD interrogation of the HVs and the characteristic waveform comprising antegrade systolic (S) and diastolic (D) waves and a retrograde (A) wave have been well described. [5] PWD interrogation of the scimitar vein demonstrates a monophasic, high-velocity waveform [Figure 2]. [6] This may be explained by the large volume of blood flowing into a compliant IVC.…”
Section: Discussionmentioning
confidence: 99%
“…Using TEE, Kirkeby-Garstad et al reported good liver anatomy visualization and an acceptable-quality image of the IVC and the RHV in 95 and 87 % of cases, respectively [10]. Meierhenrich et al [11], on the other hand, studied 34 patients scheduled for abdominal surgery and using multiplane TEE, they successfully identified the three main hepatic veins in all patients. Indeed, a number of studies support the proposition that TEE can provide good visualizations of both the IVC and RHV [12][13][14].…”
Section: Discussionmentioning
confidence: 99%